Koncepcja jedności prawa cywilnego na tle postanowień art. 2 i 384 k.c. : [The concept of unity of civil law against the background of the provisions of Articles 2 and 384 of the Civil Code] (Studia Prawnicze / The Legal Studies, 2023)
Autor artykułu przedstawia jedną z podstawowych zasad prawa cywilnego jaką jest zasada jedności prawa cywilnego w świetle regulacji prawnych art. 2 i 384 k. c. W swojej pracy szczegółowo opisuje funkcjonowanie tego rozwiązania w polskim porządku prawnym. W trakcie analizy, autor przedstawia akty normatywne wydane na podstawie art. 2 i art. 384 k. c., które zawierają upoważnienia Rady Ministrów do wydawania przepisów w zakresie obrotu uspołecznionego stanowiące wyjątek od zasady jedności prawa cywilnego. The author of this article presents one of the basic principles of civil law which is the principle of unity of civil law in the light of the legal regulations of Articles 2 and 384 of the Civil Code. His work describes in detail the functioning of this solution in the Polish legal order. In the course of the analysis, the author presents normative acts issued on the basis of Article 2 and Article 384 of the Civil Code, which contain authorisations of the Council of Ministers to issue regulations in the field of socialised trade that constitute an exception to the principle of unity of civil law.